Bone mineral density at different sites and vertebral fractures in Serbian postmenopausal women. (2nd January 2017) - Ilic Stojanovic, O.; Vuceljic, M.; Lazovic, M.; Gajic, M.; Radosavljevic, N.; Nikolic, D.; Andjic, M.; Spiroski, D.; Vujovic, S.
Abstract: Objectives: This randomized study aimed to evaluate the correlation between bone mineral densities (BMD) measured at different sites and the frequency of vertebral fractures in a group of Serbian postmenopausal women. Method: BMD was measured in 130 naïve postmenopausal women by dual X-ray absorptiometry (DXA) at the ultra-distal part of the forearms, at the hip and at the lumbar spine. At each of the measurement sites, the patients were categorized as osteoporotic, or osteopenic, or in the reference range. Vertebral fractures were examined using thoracic and lumbar spine radiography. Results: A T -score at different skeletal sites showed discordance in the site-specific region. Vertebral fractures were found in 58.82% of patients with hip osteopenia, in 45% with forearm osteopenia and in 54.54% with lumbar spine osteoporosis. Conclusions: The study confirmed that the reduction of BMD depends on age and choice of measurement site. The best correlation was obtained in the women with osteopenia at all measurement sites. The discovery of vertebral fractures by lateral thoracic and lumbar spine radiography improves prompt treatment. Reference values of BMD do not exclude vertebral fractures. Of vertebral fractures, 72.5% were asymptomatic and thus spine radiographies are obligatory. Currently discussed is the position of DXA for measuring BMD as a method of detection for patients at risk of fracture.